Changes in the Structure of Educational System in the Function of Millennium Tendencies - Kuka, Miroslav; Talevski, Jove; Jovanović, Ksenija (Richtmann Publishing, 2012)
Education in future implies a reconstruction in the education system. This practically meansimplementation of reform of the entire educational system and development of conception of thepermanent education accorded with social needs and changes. The presented work here is an integral partof a broader set up and realized preliminary project on „Redefinition of Education Structure of Republic ofSerbia“ forwarded to the Ministry of Education of the Republic of Serbia in 2010. The preliminary projectguided by Ph.D. Miroslav Kuкa and Ph.D. Vuкosava Zivкović was realized in the team work and incoordination of work of the central and regional working groups in Serbia and the surrounding countrieshaving 80 collaborators in total working on the project. Model of our structure of the education systemextends the period of compulsory education up to 10 years of age (till the first grade of high school which isthe same for all regarding the curriculum) and is based on differentiation of the education levels (frompreschool to high school) in cycles, which, on their part, are defined by aims and tasks. Short-term, middletermand long-term aims have been clearly defined and concise division of competence and the follow-upmethods of successfulness of its implementation has been made within the proposal of our model